Association of Taiwan’s Rainfall Patterns with Large-Scale Oceanic and Atmospheric Phenomena - Yi-Chun Kuo; Ming-An Lee; Mong-Ming Lu (Advances in Meteorology)
A 50-year (1960–2009) monthly rainfall gridded dataset produced by the Taiwan Climate Change Projection and Information Platform Project was presented in this study. The gridded data (5 × 5 km) displayed influence of topography on spatial variability of rainfall, and the results of the empirical orthogonal functions (EOFs) analysis revealed the patterns associated with the large-scale sea surface temperature variability over Pacific. The first mode (65%) revealed the annual peaks of large rainfall in the southwestern mountainous area, which is associated with southwest monsoons and typhoons during summertime. The second temporal EOF mode (16%) revealed the rainfall variance associated with the monsoon and its interaction with the slopes of the mountain range. This pattern is the major contributor to spatial variance of rainfall in Taiwan, as indicated by the first mode (40%) of spatial variance EOF analysis. The second temporal EOF mode correlated with the El Niño Southern Oscillation (ENSO). In particular, during the autumn of the La Niña years following the strong El Niño years, the time-varying amplitude was substantially greater than that of normal years. The third temporal EOF mode (7%) revealed a north-south out-of-phase rainfall pattern, the slowly evolving variations of which were in phase with the Pacific Decadal Oscillation. Because of Taiwan’s geographic location and the effect of local terrestrial structures, climate variability related to ENSO differed markedly from other regions in East Asia.